Resistance mechanisms and clinical characteristics of linezolid-resistant Enterococcus faecium isolates: A single-centre study in South Korea. (March 2018) - Cho, Sun Young; Kim, Hye Mee; Chung, Doo Ryeon; Kim, So Hyun; Huh, Hee Jae; Kang, Cheol-In; Peck, Kyong Ran; Lee, Nam Yong; Song, Jae-Hoon
Highlights: Data on linezolid resistance in vancomycin-resistant Enterococcus faecium (VREF) are limited. Among 389 VREF isolates, 7 (1.8%) exhibited resistance to linezolid. Two linezolid-resistant (LR)-VREF isolates from patients with previous linezolid exposure contained the G2576T mutation. Five isolates recovered from linezolid-naïve patients contained no known linezolid resistance mechanism. Linezolid use and horizontal transmission appear to be responsible for acquisition of LR-VREF. Abstract: Objectives: This study aimed to determine the prevalence of linezolid-resistant (LR) vancomycin-resistant enterococci and to investigate the mechanisms of linezolid resistance with clinical and microbiological characterisation. Methods: All vancomycin-resistant Enterococcus faecium (VREF) isolated from blood and rectal swab cultures during 2012–2015 were tested for linezolid resistance. LR-VREF isolates were tested for antimicrobial susceptibility, glycopeptide resistance genes and virulence genes. Multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) were performed. Isolates were tested for known mechanisms of linezolid resistance. Results: Among 389 VREF isolates, 7 (1.8%) were found to be resistant to linezolid. All LR-VREF isolates carried the vanA gene. Five isolates had both hyl and esp genes. The isolates were susceptible to tigecycline, daptomycin and quinupristin/dalfopristin, except for one isolate with daptomycin resistance. Two LR-VREF isolates recovered from patients with previous linezolid exposure contained the G2576T mutation in 23S rRNA and exhibited high-level resistance to linezolid (MIC > 64 mg/L). The other five isolates recovered from linezolid-naïve patients revealed no known linezolid resistance mechanism and exhibited low-level resistance to linezolid (MICs = 8–16 mg/L). Plasmid-mediated genes encoding cfr or optrA were not detected. LR-VREF isolates were represented by six different sequence types, belonging to hospital lineages, and were assigned to seven PFGE types. Conclusions: The prevalence of LR-VREF in this centre was low. Both linezolid exposure and horizontal transmission appear to be responsible for acquisition of LR-VREF in hospitalised patients. Prudent use of linezolid and improved infection control strategies are needed to limit the spread of LR-VREF.